Modern Clinical and Biochemical Characteristics of Liver Cirrhosis Patients of Viral Etiology with Spontaneous Bacterial Peritonitis (Texas Journal of Medical Science, 2022)
The clinical and laboratorical characteristics of spontaneous bacterial peritonitis with cirrhosis of the liver of viral etiology were studied. A total of 58 (32 (55.2%) men and 26 (40.6%) women) patients with cirrhosis of the liver of viral etiology aged 30 to 69 years were examined. Upon admission, all patients underwent diagnostic laparocentesis, followed by counting the number of neutrophils in the AF and plating on culture media. It was established in the examined patients that cirrhosis with HCV markers was most frequently encountered. An analysis of the infection factors in the examined patients with liver cirrhosis with complicated SBP showed that problems associated with parenteral interventions were noted by 67.3% and the source of infection was not established in 24.1% of patients. The most common signs of SBP were dyspeptic symptoms-60.3%, fever-37.9%, leukocytosis with the appearance of immature forms of leukocytes-48.2%.